Association between severe unaddressed dental needs and developmental health at school entry in Canada: a cross-sectional study - Magdalena Janus; Caroline Reid-Westoby; Catherine Lee; Marni Brownell; Jonathon L. Maguire (BMC, 2019)
Abstract Background Dental problems are the most prevalent chronic disease worldwide, with up to half of all kindergarten children having tooth decay. However, there is a lack of evidence of whether unaddressed dental needs (UDNs) are associated with children's developmental health, a concept reflecting holistic child development - encompassing physical, emotional, and cognitive development. The objective of the current study was to evaluate the relationship between UDNs and developmental health among kindergarten children using the Early Development Instrument (EDI). Methods We examined associations between teacher reported UDNs and developmental vulnerability on the EDI. Children were included in the study if they were enrolled in kindergarten in publicly-funded schools in Canada between 2010 and 2015, had been in the classroom for at least one month, and had no more than 25% of missing items on the questionnaire. Results Among 576,264 children who met inclusion criteria (95.4% of eligible children), 2465 (0.4%) were identified as having UDNs by their teachers. Children with UDNs had 4.58 to 8.27 times higher odds of being vulnerable on any of the five developmental domains (physical health and well-being, social competence, emotional maturity, language and cognitive development, communication skills and general knowledge), compared to children without UDNs. Conclusion In this study, teacher-reported UDNs were associated with developmental vulnerability in kindergarten children. Teacher reported unmet dental needs in kindergarten children may be a proxy for poor developmental health at school entry, and thus a marker for supporting both children's oral health and early developmental needs.